Characterization of the complete chloroplast genome sequence of Pueraria montana var. lobata and its phylogenetic implications. Issue 1 (2nd January 2019) - Zhang, Zhiyong; Tang, Tianming; Zhu, Piao; Chen, Ying; Jiang, Xuebo; Zeng, Yanling; Li, Ling
Abstract: Pueraria montana var . lobata is a traditional Chinese herb with various medicinal purposes. In this study, the complete chloroplast genome of the P. montana var . lobata was obtained by using Illumina HiSeq X Ten. The chloroplast genome was 153, 411 bp long, which consisted of a large single-copy (LSC) region of 84, 131 bp and a short single-copy (SSC) region of 17, 990 bp separated by a pair of inverted repeat (IR) regions of 25, 645 bp. The whole chloroplast genome contained 111 gene species including 77 protein-coding genes (PCG), 30 tRNA, and 4 rRNA species, with 19 of them occurring in double copies. Introns were detected in 12 PCG and 6 tRNA species. The overall GC content is 35.4%. Phylogenetic analysis indicated that P. montana var . lobata was relatively close to Pachyrhizus erosus in phylogeny.